Evaluation of Optimal Roof Form in the Esfahan City Using Wind Tower - Elahe MohammadRezaei; Meghedi Khodabakhshian (توسعه پایدار شهری)
The hierarchy of climatic design in a region has an important role in the condition of environmental comfort. In contemporary times, climatic design is a logical response to the crisis of the shortage in energy resources and increasing environmental pollutions, which are caused by using fossil fuel. This issue is crucial in the areas with specific climate. Attention to the main goals of climatic design in each region and predicting some items in order to realize the goals, leads to compatibility and harmony between buildings and climate, and it leads to reduce energy consumption. The mentioned issue has background of several thousand years, especially in Iran. Hot and dry regions of Iran have harsh climate since attention to environment is important to achieve thermal comfort and compatibility of climate and architecture. By considering the strategies of the climatic design, this research evaluating the optimal form of roof to use natural ventilation in Esfahan. There is limited airflow around the body of compact buildings, therefore the roof has fundamental role in ventilation. In this research three different types of roofs including curved, sloped and flat roof are simulated, and their ability in optimization of natural ventilation is investigated. The research methodology is descriptive analysis and the data is collected from meteorological station and documentary resources. Moreover, “Flow Design Autodesk” was applied as a software for the computer simulation.